IMPLEMENTASI SKEMA STEGANOGRAFI DENGAN METODE SELECT LEAST SIGNIFICANT BITS (SLSB) PADA PESAN TERENKRIPSI UNTUK PENGIRIMAN MMS - , E. HAODUDIN NURKFILI ([Yogyakarta] : Universitas Gadjah Mada, 2012)
This research explains Steganography uses scheme Select Least Significant Bits (SLSB). The messages to be inserted are an original message, a compressed message, an encrypted message, and the compressed and encrypted message. The Encryption uses ElGamal ECC Algorithm and compression uses Huffman Code Algorithm. Process on Steganography system: The insertion of one bit per pixel, two bits per pixel and three bits per pixel. The experiment is used to know requirement of bit: original message 150 characters equal to 1200 bits. The compressed message has saved bits until 50,8%. The addition of bits having performed the encryption message average increasing five-fold of original message, reduction of bits successfully with uses combining compression and encryption on the message, reduction saving 55.3% of bits. Tree from Huffman Code requires an average of 12464bits. The experiments to know reliability of Steganography image use Histogram Analysis, RS Analysis and objective image quality measurement. Histogram not able to detect a Steganography image, of ten our experiment on bitmap images have the results histogram Steganography not much different from the original image. The results with RS analysis doesnât different from the estimate value of the original image. Last experiment uses an objective image quality measurement is based tolerance error in the image. Parameters are used: Mean Square Error (MSE), Peak Signal to Noise Ratio (PSNR in dB), Normalized Cross-Correlation (NCC), Average Difference (AD), Structural Content (SC), Maximum Difference (MD), and Normalized Absolute Error (NAE). Experiment the quality of the image shows all the images Steganography having the value of tolerance error that is not much different from the value of tolerance error of the original image.